2022
DOI: 10.1111/liv.15198
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glomerular filtration rate in patients with cirrhosis: Available tools and perspectives

Abstract: Renal dysfunction is frequent in cirrhotic patients and is associated with a worse prognosis. 1 Cirrhotic patients share with the general population common aetiologies of kidney dysfunction, including pre-renal, intrinsic and post-renal causes of acute kidney injury (AKI), as well as all the known causes of chronic kidney disease (CKD), such as diabetic or hypertensive nephropathy. 2 Additionally, they may suffer from a specific kind of renal dysfunction, hepatorenal syndrome (HRS). 3,4 Among patients hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…Hepatorenal syndrome (HRS) is a clinical picture usually accompanied by acute renal failure in patients with acute or chronic liver disease. Although it is usually seen in patients with advanced cirrhosis, it can also be seen in portal hypertension due to metastatic tumors [18][19][20][21]. Since our study was retrospective, although HRS was not diagnosed by considering the diagnostic criteria, it was shown that adding hepatic dysfunction to renal failure reduces patient survival.…”
Section: Discussionmentioning
confidence: 91%
“…Hepatorenal syndrome (HRS) is a clinical picture usually accompanied by acute renal failure in patients with acute or chronic liver disease. Although it is usually seen in patients with advanced cirrhosis, it can also be seen in portal hypertension due to metastatic tumors [18][19][20][21]. Since our study was retrospective, although HRS was not diagnosed by considering the diagnostic criteria, it was shown that adding hepatic dysfunction to renal failure reduces patient survival.…”
Section: Discussionmentioning
confidence: 91%
“…Creatinine is a product of creatine phosphate metabolism in skeletal muscle and is freely filtered by the glomerulus. Creatinine measurement is cheap, yields rapid results, and is widely available 19 . As previously mentioned, the current…”
Section: Diagnosis and Management Limitations Of Serum Creatininementioning
confidence: 99%
“…Moreover, specific features in patients with cirrhosis affect serum creatinine levels 19,23,24 . For instance, both sarcopenia, which is associated with reduced production of creatinine, and ascites, which increases the total volume of distribution, lead to an overestimation of GFR 23,25 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this issue of Liver International , Campion and colleagues present a much‐needed, detailed and comprehensive review that brings clarity as to available tools to estimate GFR in patients with cirrhosis, highlighting major advantages and flaws for each available method 8 . Whilst serum creatinine remains an imperfect tool to estimate kidney function in both acute and chronic kidney disease, it is standardized, cheap and widely available.…”
Section: Figurementioning
confidence: 99%
“…In this issue of Liver International, Campion and colleagues present a much-needed, detailed and comprehensive review that brings clarity as to available tools to estimate GFR in patients with cirrhosis, highlighting major advantages and flaws for each available method. 8 Whilst serum creatinine remains an imperfect tool to estimate kidney function in both acute and chronic kidney disease, it is standardized, cheap and widely available. In fact, the very definitions we use for acute kidney injury (AKI) in cirrhosis, hepatorenal syndrome and acute-on-chronic liver failure are based on serum creatinine values, and all have excellent correlation with short-and long-term prognosis.…”
Section: Assessment Of Kidney Function In Cirrhosis: Are We Moving Cl...mentioning
confidence: 99%